PENGARUH JOB EMBEDDEDNESS TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Maharani, Agnesia; Satria, Dias (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research investigates the impact of job embeddedness on organizational citizenship behavior among workers in Banyuwangi Regency in 2024. Job embeddedness includes employees' connections with the organization, value congruence, and personal sacrifices to remain employed. Organizational citizenship behavior refers to individual contributions that exceed formal job requirements, such as helping colleagues and participating in organizational activities. The research method used is quantitative with a survey approach. Data were collected from a sample of workers in Banyuwangi Regency and analyzed using statistical techniques. The results showed that job embeddedness significantly influences organizational citizenship behavior. Employees who feel attached to their jobs tend to be more active and contribute more to organizational activities. The implications of this research highlight the importance for organizational management to enhance job embeddedness to promote positive organizational citizenship behavior. Organizations can achieve this by creating a supportive work environment, providing training, and appropriate incentives.